Histirical Narrative in Urdu Novel - Nazia Parveen (بازیافت)
Language  is  the  only  source  of  tranquility  and  accomplishment for humanity  since  ancient  times.  Epiphany  fortifies the expressive ability of a language. An author narrates a story in various ways according to his/her own will. This way of expressing thoughts in words  is  known  as  narration. Narration  is  the  canvas  which  portrays romantic,  political,  historical,  religious,  social  and  cultural  concepts. This  article  unveils the discussion pertaining to historical, mythological  and  archival  narrations.  Shams-ur-Rahman’s novel “Kei Chand thy Sar-e-Asmaan”, Mirza Hamid Baig’s novel “Anarkali”, Waheed   Ahmad ’s   novel  “Zeeno”,  Yaqoob  Yawar’s  novel “Ezazeel” and  Fahmida  Riaz’s  novel “Qilah  Framoshi” are  the finest examples of  archival  and  myhological  narrations.